STRATEGI KEMENTERIAN PARIWISATA INDONESIA DALAM MENINGKATKAN BRANDING WISATA HALAL - Elpa Hermawan (Unitri Press, 2019)
This study aims to determine the strategy of the Indonesian Ministry of Tourism in increasing halal tourism branding to become the best tourist destination in the world and it is increasing the number of tourists both domestically and abroad. Halal tourism is one of the tourism concepts models that has the principle of regularity in accordance with the teachings of the Muslim community. This study used qualitative research methods. The data analysis technique consists of three steps, namely data reduction, data presentation and drawing conclusions. The results showed that the nine strategies have been used by the government are the appropriate strategies to implement ten superior programs in improving halal tourism in Indonesia. The strategy used to achieve the overall vision includes all aspects of needs starting from the aspect of the destination, marketing aspects, and aspects of human resources, society, and industry. Each strategy is implemented with programs that are aligned through the utilization of technological advances. The implications of these strategies can make Indonesian halal tourism become the best world-class tourism.